Addition Homo‐ and Copolymerizations of Dicyclopentadiene and 5‐n‐Hexylnorbornene in the Presence of Pd‐N‐Heterocyclic Carbene Complexes. Issue 24 (5th November 2018) - Wozniak, Alyona I.; Bermesheva, Evgeniya V.; Gavrilova, Natalia N.; Ilyasov, Igor R.; Nechaev, Mikhail S.; Asachenko, Andrey F.; Topchiy, Maxim A.; Gribanov, Pavel S.; Bermeshev, Maxim V.
Abstract: Herein for the first time addition homopolymerization of dicyclopentadiene (DCPD) and its copolymerization with 5‐ n ‐hexylnorbornene in the presence of different Pd‐N‐heterocyclic carbene complexes activated by a borate (Na + [B(3, 5‐(CF3 )2 C6 H5 )4 ] − (NaBARF)) or methylaluminoxane (MAO) are investigated. It is found that systems based on Pd‐N‐heterocyclic carbene complex in combination with NaBARF or MAO are effective catalysts and a Pd‐N‐heterocyclic carbene complex/NaBARF system allows for the addition polymerization of these monomers in air. The influence of the N‐heterocyclic carbene structure, the nature of cocatalyst, and solvent on the catalyst activity of a system based on Pd‐N‐heterocyclic carbene complex are determined. The properties of the obtained addition polydicyclopentadiene (poly(DCPD)) such as thermal stability, solid‐state structure, and porosity are studied. The synthesized poly(DCPD) possesses Brunauer, Emmett, and Teller surface area as high as 155 m 2 g −1 and so addition polymerization of DCPD can be considered as a single‐step and convenient way to synthesize of porous polymers from a norbornene derivative. Abstract : Addition polymerization of dicyclopentadiene and its copolymerization with 5‐ n ‐hexylnorbornene was studied in the presence of five Pd‐N‐heterocyclic carbene complexes in combination with PCy3 and NaBARF or MAO as cocatalyst. Pd‐complex/PCy3 /NaBARF systems were found to be effective catalysts and polymerized monomers in air and in wet conditions. New relationships between Pd‐complex structure and its catalyst activity were disclosed.